2021
DOI: 10.37394/23207.2021.18.89
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 Pandemic On Local Rice Supply Chain FlowPatterns In Kapuas Regency, Central Kalimantan, Indonesia

Abstract: The fact that the pandemic condition due to Covid-19 that broke out in early 2020 has caught the attention of various elements of society. The visible impact is not only on public health, but also influences the distribution and availability of various food supplies, especially local rice in the study area. The purpose of this study was to examine the flow patterns of the local rice supply chain during the Covid-19 pandemic. Data analysis using supply chain analysis of Supply Chain management (SCM). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These postulates are fully attributable to the Latvian population, which has been demonstrated by the study. Some relevant studies about COVID-19 in other countries can be found in [94][95][96].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…These postulates are fully attributable to the Latvian population, which has been demonstrated by the study. Some relevant studies about COVID-19 in other countries can be found in [94][95][96].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Such actions strained the midstream and downstream segments of the FSC, resulting in a total disruption [20]. The intermediary market actors play a major role in food distribution, especially in highly populated regions in Asia, whereby they are accountable for the marketability of food products and manage transaction costs made up of logistics activities [21][22][23]. Marketplaces were closed to prevent the transmission of the virus during the pandemic [20].…”
Section: Introductionmentioning
confidence: 99%
“…Rice prices did not change in the early months of the pandemic in Indonesia (Nasir et al, 2021); however, as the health emergency progressed, distributors and wholesalers incurred additional costs due to pandemic-induced mobility restrictions (Erlina and Elbaar, 2021). In the Philippines, San Juan (2021) argues that the global rice supply disruption due to the pandemic proves that the country cannot heavily rely on rice imports; instead, it should work on strengthening its domestic rice supply.…”
mentioning
confidence: 99%